The Analysis of CodeMixing in Lyrics of Rungkad - Handayani, Cici (Universitas Syiah Kuala, 2024)
In 1940 there is a song with title Kopral Jono that put code mixing in the lyrics Aksimu bungvery goodseperti masRobin Hood. In 2024 code mixing can be found in a lot of songs, one of them is Rungkad created by Vicky Tri Prasetyo and popularized by Nella Kharisma. This research is conducted to find the forms of code mixing and the factors causing code mixing. The data collection technique in this research uses two techniques, namely reading and note-taking techniques. The data collection procedure is by reading the song lyrics, marking words, phrases, clauses, word repetitions, idioms, basters which indicate code mixing, noting the marked words, phrases, clauses, sentences, and then grouping the data which indicates code mixing according to the research problem. In Rungkad song there are 39 data of code mixing found in the form of inserting word element for 27 data, inserting phrase elements for 9 data and, inserting clause elements for 3 data. Meanwhile, for code mixing, inserting bastards, idioms and repetitions elements were not found at all. The form of code mixing in the Rungkad song lyrics is dominated by the form of code mixing in the form of inserting word elements, while the choice of language varieties is dominated by Javanese and Indonesian. The factors that cause code mixing in the song lyrics are speaker factors and language factors.Keywords: Code Mixing, Forms and Factors, Lyrics Rungkad Dangdut Songs